High Prevalence of Hyper-Aerotolerant Campylobacter jejuni in Retail Poultry with Potential Implication in Human Infection - Oh, Euna; McMullen, Lynn; Jeon, Byeonghwa (Frontiers in Microbiology, 2015)
Campylobacter jejuni is a leading cause of foodborne illnesses around the world. Since C. jejuni is microaerophilic and sensitive to oxygen, aerotolerance is important in the transmission of C. jejuni to humans via foods under aerobic conditions. In this study, 70 C. jejuni strains were isolated from retail raw chicken meats and were subject to multilocus sequence typing (MLST) analysis. In the aerotolerance testing by aerobic shaking at 200 rpm, 50 (71.4%) isolates survived after 12 h (i.e., aerotolerant), whereas 20 (28.6%) isolates did not (i.e. aerosensitive). Interestingly, further aerobic cultivation showed that 25 (35.7%) isolates still survived even after 24 h of vigorous aerobic shaking (i.e., hyper-aerotolerant). Compared to aerosensitive strains, the hyper-aerotolerant strains exhibited increased resistance to oxidative stress, both peroxide and superoxide. A mutation of ahpC in hyper-aerotolerant strains significantly impaired aerotolerance, indicating oxidative stress defense plays an important role in hyper-aerotolerance. The aerotolerant and hyper-aerotolerant strains were primarily classified into MLST clonal complexes (CCs)-21 and -45, which are known to be the major CCs implicated in human gastroenteritis. Compared to the aerosensitive strains, CC-21 was more dominant than CC-45 in aerotolerant and hyper-aerotolerant strains. The findings in this study revealed that hyper-aerotolerant C. jejuni is highly prevalent in raw chicken meats. The enhanced aerotolerance in C. jejuni would impact human infection by increasing possibilities of the foodborne transmission of C. jejuni under aerobic conditions.